Think Before They Squeak: Vocalizations of the Squirrel Family - Newar, Sasha L.; Bowman, Jeff (Frontiers in Ecology and Evolution, 2020)
Squirrels (Sciuridae) are a diverse group in behavior, morphology, and ecology. This variation is typified by the wide range of vocalizations spanning ground squirrels (Marmotini and Xerini), tree squirrels (Callosciurinae and Sciurini), and flying squirrels (Pteromyini). Squirrels produce calls that range in frequency, modulation, and function, with a complex set of social calls occurring across the family. We review the history of recording methods used in the development of squirrel vocalization repertoires, with emphasis on how the ecology and methodology impact the frequency values reported. The fundamental (F0 – the mean frequency of the fundamental harmonic), dominant (FDom – the frequency of maximum energy or amplitude), minimum (FMin – the minimum frequency of the fundamental harmonic), maximum (FMax – the maximum frequency of the dominant harmonic), and highest harmonic (FHarm – the mean frequency of the highest visible harmonic) frequencies were considered against popular hypotheses that have attempted to explain the evolution of vocal frequency characteristics in terrestrial mammals. These hypotheses include body size, predator avoidance, habitat type, and diel activity pattern. Phylogenetic generalized least squared modeling revealed that body mass and the frequency limits of the methods were the strongest drivers of high-frequency communication. Consistent with popular hypotheses, social squirrels exhibited a broader range of F0, FDom, and FMax than solitary squirrels while habitat openness promoted higher FDom and FHarm. Additionally, nocturnality was significantly associated with higher F0, FDom, and FMax, suggesting that flying squirrels, the only nocturnal squirrels, commonly use high-frequency acoustic signals, a finding that merits further investigation. In conclusion, our review provides a unique insight into the role of behavioral ecology on vocal repertoires and the importance of accurate equipment selection for sampling across a diverse taxon.